Lipid production under a nutrient-sufficient condition outperforms starvation conditions due to a natural polarization of lipid content in algal biofilm - Sungwhan Kim (6369095) (2023)
Attached algae cultivation for biofuel production has received proliferated attention given its advantage to reduce harvesting/dewatering costs and contamination risk. In this study, the effects of various nutrient starvation strategies on lipid production through the attached cultivation of Ettlia sp. YC001 was investigated. A detailed study on compositional variation over the depth of biofilms was followed to understand the phenomena within the biofilms under various nutrient conditions. As a result, the nutrient starvation strategy enhanced the lipid content of biofilms by 3–7 %, however, it limited biomass growth significantly. Ultimately, lipid production with sufficient nutrient supply outperformed those with nutrient starvations, reaching up to the maximum lipid productivity of 6.5 ± 0.1 g/m2/day. Compositional analyses over the depth of biofilms identified that high lipid accumulation was induced in the top layer of the biofilm regardless of medium condition as the top layers were naturally under stress from nutrient deficiency and high light exposure. Other Information Published in: Fuel License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.fuel.2022.126902